Measurements of the Flow in Backshroud/Casing Clearance of Precessing Centrifugal Impeller - Yoshiki Yoshida; Yoshinobu Tsujimoto; Hideo Ohashi; Akira Saito; Shin Ishizaki (International Journal of Rotating Machinery)
Detailed flow measurements have been made to clarify the unsteady flow in the backshroud/ casing clearance of a precessing centrifugal impeller. The unsteady pressure was integrated to obtain the fluid force moment on the precessing impeller shroud for various precessing frequencies. It was shown that the fluid force moment can become rotordynamically destabilizing for small forward precessing motion as originally found by Ohashi et al. The effects of leakage flow in the backshroud/casing clearance and a gap between impeller side plate and casing at the impeller outlet are clearly shown, and the discussions are also made based on the unsteady velocity and pressure measurements.